2019
DOI: 10.1016/j.ijantimicag.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

High-dose trimethoprim-sulfamethoxazole and clindamycin for Staphylococcus aureus endocarditis

Abstract: Objective: The mortality rate from Staphylococcus aureus endocarditis remains as high as 20-30% despite better medical and surgical treatment. This study evaluates the efficiency and tolerance of a combination of trimethoprim-sulfamethoxazole and clindamycin (T&C) +/rifampicin and gentamicin, with rapid switch to oral T&C. Methods: Before-after intervention study to compare the outcome of 170 control patients before the introduction of the T&C protocol (2001 to 2011) to 171 patients in the T&C group (2012 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 32 publications
2
30
0
1
Order By: Relevance
“…Staphylococcus spp. (MRSA and non-MRSA) are considered susceptible to trimethoprim/sulfamethoxazole; however, several studies, including ours, have reported the isolation of trimethoprim/sulfamethoxazole-resistant MRSA and non-MRSA strains from patients ( Harris et al, 2018 , Sato et al, 2018 , Coombs et al, 2019 , Tissot-Dupont et al, 2019 ). In fact, mutability of the Staphylococcus strains, including MRSA strains is a very perplexing issue.…”
Section: Discussionmentioning
confidence: 80%
“…Staphylococcus spp. (MRSA and non-MRSA) are considered susceptible to trimethoprim/sulfamethoxazole; however, several studies, including ours, have reported the isolation of trimethoprim/sulfamethoxazole-resistant MRSA and non-MRSA strains from patients ( Harris et al, 2018 , Sato et al, 2018 , Coombs et al, 2019 , Tissot-Dupont et al, 2019 ). In fact, mutability of the Staphylococcus strains, including MRSA strains is a very perplexing issue.…”
Section: Discussionmentioning
confidence: 80%
“…In turn, MRSA remains susceptible to lincosamides, which are second-line treatments for MRSA, at levels close to 50% of susceptibility. 45,46 Although VAN is the firstchoice antimicrobial for MRSA bacteraemia, 46 there are other treatment alternatives, such as LZD, SXT and CLI, in monotherapy or in combination with DAP or ceftaroline (CPT). [45][46][47][48] Therefore, interpretive reading of the antibiograms and the usage of first-choice antimicrobials are essential to reduce the risk of therapeutic failure and increase resistance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies had reported similar results. Tissot-Dupont et al (2019) reported that TMP-SMX did not achieve noninferiority compared with vancomycin among patients with invasive MRSA infections. There were also some different conclusions.…”
Section: Discussionmentioning
confidence: 99%